Moscow Everyday Life in Soviet Film Comedies of the 1960s–1980s - Kozhabergenova, Anel (Slavica, 2026)
The paper addresses the representation of everyday life in Soviet film comedies of the 1960s–1980s. The object of analysis is a corpus of nine films: Vzroslye deti [Adult children] (1961), Legkaya zhizn [Easy life] (1964), Daite zhalobnuyu knigu [Give me a book for complaints] (1965), Uroki literatury [Literature lessons] (1968), Ironiya sudby, ili S legkim parom! [The irony of fate, or Enjoy your bath!] (1975), Mimino (1977), Po semeynym obstoyatelstvam [Due to family circumstances] (1977), Sluzhebny roman [Office romance] (1977), and Samaya obayatelnaya i privlekatelnaya [The most charming and attractive] (1985). The research methodology combines two complementary approaches: Michel de Certeau’s sociology of everyday life and Gaston Bachelard’s phenomenological poetics of space. De Certeau’s concept of tactics and strategies helps describe the mechanisms by which the Soviet urban citizen adapted themselves to systemic structures, while Bachelard’s ideas on poetics enable the reading of interiors, material objects, and living spaces as symbolic images rooted in memory and imagination. The article demonstrates that the Soviet film comedy of this period was not a degraded genre but a distinct aesthetic form linked to Italian Neorealism that developed its own language for representing the everyday. In the analyzed films, Moscow appears not as a neutral topographical backdrop but as a meaning-making space that captures the profound transformations of late Soviet society: the conflict of generations, the crisis of public and private spheres, and the paradoxes of urban space unification. Film comedy is treated both as an archive of social tactics and as a text-space where the social and the symbolic are inseparably intertwined.